Hydrogen Peroxide Treatment and the Phenylpropanoid Pathway Precursors Feeding Improve Phenolics and Antioxidant Capacity of Quinoa Sprouts via an Induction of L-Tyrosine and L-Phenylalanine Ammonia-Lyases Activities - Michał Świeca (Journal of Chemistry)
Hydrogen peroxide treatment and the phenylpropanoid pathway precursors feeding affected the antioxidant capacity of quinoa sprouts. Compared to the control, total phenolics content was significantly increased by treatment of control sprouts with 50 mM and 200 mM H2O2—an elevation of about 24% and 28%, respectively. The highest increase of flavonoids content was found for the sprouts treated with 200 mM H2O2 obtained from seeds fed with shikimic acid. All the studied modifications increased the antioxidant potential of sprouts (at least by 50% compared to control). The highest reducing power was found for the sprouts treated with 200 mM H2O2 obtained by phenylalanine feeding (5.03 mg TE/g DW) and those obtained from the seeds fed with tyrosine (5.26 mg TE/g DW). The activities of L-tyrosine (TAL) and L-phenylalanine (PAL) ammonia-lyases were strongly affected by germination time as well as the applied modification of sprouting. On the 3rd day the highest PAL activity was determined for both untreated and induced with 50 mM H2O2 sprouts obtained by phenylalanine feeding. H2O2 induced TAL activity; the highest TAL activity was determined for 3-day-old sprouts induced with 200 mM H2O2 obtained from seeds fed with phenylalanine.